REBECCA BLOOMWOOD’S EFFORTS TO COPE WITH HER PSYCHOLOGICAL PROBLEM IN CONFESSIONS OF SHOPAHOLIC THE MOVIE - HENDARYANI, REVITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : psychological, id, ego, super ego, defense mechanism, mise-en-sceneLiterature has a close relationship with psychology. They have the same object, that is human being. In the development of literature, movie is a form of entertainment that enacts a story by sound and a sequence of images giving the illusion of continuous movement. Confessions of Shopaholic the movie tells about the struggle of a woman as the main character who suffers psychological problem when she is at the shop. She wants to buy many things that she want. She still loves shopping even though she was being chased by a debt collector.This research uses qualitative approach to analyze the object of the study. Freudian psychoanalysis theory used to solve the problem that is the psychological problem faced by Rebecca and how she copes with her psychological problem. Defense mechanism is the strategy developed by the ego to protect against anxiety. Defense mechanisms are expected to keep the mind against feeling and thoughts that are too hard for conscious mind to overcome. The writer also analyzes the mise-en-scene of each scene to help her understand more about the Rebecca’s personality. Mise-en-scene refers to all objects in a specific frame and character primarily refers to the composition of the frame.The research shows that Rebecca has psychological problem that is anxiety.She does a denial as a defense mechanism for relieving her id. However she is finally able to cope with her psychological problem by watching the tutorial from the author of “Control Your Urge to Shop” by Garret E. Barton, joining the shopaholic community, write “The Girl with Green scarf”, sell all her goods that she has bought by her credit card to pay her debts.Furthermore, the writer suggests the next researcher to analyze other aspects like defense mechanism that arise in Confessions of Shopaholic movie. It is because there are still many aspects that can be explored by using different theory approaches such as semiotics.